Prevalence of self-injury, suicidal ideation, plans and attempts in adolescents aged 13 to 19 years of age - Pawłowska, Beata; Potembska, Emilia; Zygo, Maciej; Olajossy, Marcin (Polish Journal of Public Health, 2015)
Introduction. Increased suicide rates, both among adults and adolescents, have been seen in Poland over recent years. Aim. The aim of the study was to determine the prevalence of self-injury, suicide ideation, plans and attempts in adolescents aged 13 to 19 years. Material and methods. The study encompassed the total number of 6883 individuals aged 13 to 19 years, 69% of them being girls and 31% – boys. All respondents lived in Lubelskie Province. The research was conducted using a questionnaire designed by the authors. Results. In the group composed of 6883 adolescents living in Lublin Province, suicide ideation was reported by 47.65% of the respondents, suicide plans by 32.35%, suicide attempts were carried out by 10% of adolescents and self-injury by 24.91% of the respondents aged 13 to 19 years. Conclusions. The greatest prevalence of suicide ideation, plans and attempts, as well as self-injuries, were recorded in the group of adolescents aged 17. The adolescents living in the urban areas are more likely to inflict self-injury than those living in rural areas. Furthermore, adolescents with suicidal tendencies, e.g. attempting suicide and self-injury, are more prone to alcohol and substance abuse. It needs emphasizing that many adolescents with suicidal tendencies, compared against those who did not carry them out, have past experience of psychological, physical and sexual violence in the family, have been raised by a single parent or in families, where one of the parents abused alcohol.